Variation in the Impact of New York on Pause on Traffic Congestion by Racialized Economic Segregation and Environmental Burden - Jenni A. Shearston; Roheeni Saxena; Joan A. Casey; Marianthi‐Anna Kioumourtzoglou; Markus Hilpert (GeoHealth)
Abstract During the 2019 coronavirus pandemic, stay‐at‐home policies such as New York's (NY) NY on Pause dramatically reduced traffic congestion. Despite high traffic burden in NY's environmental justice communities, this reduction has not been evaluated through an environmental justice lens—our objective in this analysis. We obtained census tract‐level traffic congestion data from Google traffic maps hourly for 2018–2020. We defined congestion as the percent of streets in a census tract with heavy traffic (red‐ or maroon‐color). We used the Index of Concentration at the Extremes (ICE) to measure racialized economic segregation and the CDC's Environmental Justice Index (EJI) as a measure of combined environmental, social, and chronic disease burden. We divided census tracts into quintiles of ICE and EJI and used linear mixed models stratified by ICE and EJI quintile in an interrupted time series design. Prior to NY on Pause, less marginalized and burdened census tracts (Q5) tended to have higher levels of traffic congestion; during NY on Pause, this trend reversed. For both ICE and EJI, more marginalized and burdened (Q1–Q2 vs. Q4–Q5) tracts had smaller absolute decreases in percent traffic congestion. For example, percent traffic congestion in ICE Q5 decreased by 7.8% (% change: −36.6%), but in Q1, it decreased by 4.2% (% change: −51.7%). NY on Pause, while protecting residents during COVID‐19, may have resulted in inequitable reductions in traffic congestion. It is critical that such inequities are measured and acknowledged so that future policies to reduce traffic congestion and respond to pandemics can enhance equity.